Varian Makna Dosa dalam Al-Qur’an : Studi Tafsir Tentang Lafadh Al-Dhanb dan Al-Ithm - Fajrul Islam, Ahmad Fakhruddin; Salim, M. Nur (Program Studi Pendidikan Agama Islam, Fakultas Agama Islam, Universitas Hasyim Asy'ari Tebuireng Jombang, Indonesia, 2021)
Abstract: Al-Qur'an describes various forms of sin both applicatively and implicitly. but from various forms of different meanings. These all have a common thread of meaning so that in short it is immediately interpreted as sin. Although in fact there are many differences in understanding the essence of the sentences of the Qur'an which are interpreted as sin. The unification of meaning into one meaning, namely sin, makes the writer feel uneasy because reality has different applications and implications. Departing from a reflection to explore the true meaning that is appropriate to be attached to the pronunciation al-ithm and al-dhanb which have the meaning of sin. This happens because the author observes that many people understand and know what sin means, but understanding it will lead to different meanings and explanations. This happens because of various aspects which are even closely related to sin. This study is focusing to explore the true meaning of the pronunciation al-ithm and al-dhanb which are usually interpreted as sin, even though the two actually have differences. This research finally resulted in what the authors were looking for, namely the difference in the operational meanings of the two pronunciations that originated from the interpretation of the Al-Qur'an verse.